Spot's noisy farm - Hill, Eric (Frederick Warne London, 2012)
Spot spends the day on a farm with his Dad. He has so much fun, rumbling round the farm and discovering different animals and the sounds they make! Young readers can press the sound button on every page to hear the tractor's sound